Functional Biomolecules in Animal Nutrition: Biochemical Mechanisms and Their Impacts on Growth Performance and Health Outcomes - Md. Emran Hossain (International Journal of Nutritions, 2026)
Functional biomolecules have emerged as critical modulators of animal nutrition, extending beyond conventional nutrient supply to regulate biochemical and physiological processes that determine growth performance and health outcomes. This review synthesizes current knowledge on diverse classes of bioactive compounds, including amino acids, peptides, fatty acids, vitamins, minerals, phytochemicals, and microbial-derived metabolites, and their roles in livestock systems. Emphasis is placed on underlying biochemical mechanisms such as enzyme activation, nutrient signaling pathways, gene expression modulation, and antioxidant defense systems. These biomolecules influence key metabolic pathways involved in protein synthesis, energy utilization, lipid metabolism, and immune function. Recent advances highlight the interaction between functional biomolecules and the gut microbiome, where microbial fermentation products and host microbe crosstalk contribute to improved nutrient digestibility, intestinal integrity, and disease resistance. Evidence demonstrates that strategic inclusion of functional biomolecules enhances feed efficiency, promotes muscle growth, supports reproductive performance, and mitigates metabolic and oxidative stress-related disorders. In addition, these compounds serve as effective alternatives to antibiotic growth promoters, aligning with global efforts toward sustainable and responsible livestock production. The integration of omics technologies, including metabolomics and proteomics, has further advanced the understanding of biomolecule-driven nutritional regulation, enabling precision feeding strategies tailored to species, production stage, and environmental conditions. However, challenges remain regarding bioavailability, dosage optimization, variability in responses, and economic feasibility. Future research should focus on mechanistic validation, the development of cost-effective delivery systems, and field-level applications. Overall, functional biomolecules represent a promising avenue for enhancing livestock productivity, health, and sustainability through targeted nutritional biochemistry.
Keywords: Animal Health; Bioactive compounds; feed efficiency; growth performance; metabolomics; nutritional biochemistry